The Negotiation of Space and Rights: Suburban Planning with Diversity - Zhuang, Zhixi Cecilia (2021)
The increasing suburbanization of immigrant settlement in Canada’s major receiving cities has created unprecedented challenges for municipalities. Despite emerging research about the rise of ethnic suburbs in Canada and abroad, the role of suburban municipalities in facilitating immigrant integration and planning with diversity remains unclear. Based on mixed-method ethnographic research, this article investigates how immigrant and racialized communities in the Greater Toronto Area have significantly transformed suburban places and built institutionally complete communities. However, the rapid development of these spaces has not been fully recognized or supported by municipal planning authorities. Conflicts related to land use, public engagement, and public realm development expose planning’s failure to keep pace with the diverse needs of immigrant communities, who must continually negotiate and fight for their use of space. Furthermore, the lack of effective civic engagement not only ignores immigrant and racialized communities as important stakeholders in suburban redevelopment, but also threatens to destroy the social infrastructure built by these communities and their ‘informal’ practices that are often not recognized by the planning ‘norm.’ Without appropriate community consultation, planning processes can further sideline marginalized groups. Lack of consultation also tends to prevent cooperation between groups, impeding the building of inclusive communities. It is imperative for municipalities to better understand and encourage community engagement and placemaking in ethnic suburbs. This study offers several recommendations for suburban planning with diversity.